A Distributed Energy-Efficient Clustering Routing Protocol with Dynamic Round-Length for Wireless Sensor Networks - Oubadi, Sihem; Derdouri, Lakhdar; Laboudi, Zakaria; Demri, Mohammed (Engineering, Technology & Applied Science Research, 2025)
Due to resource constraints, especially limited energy and network dynamics, the design and implementation of efficient and reliable routing protocols for Wireless Sensor Networks (WSNs) has become a challenging task. Several routing protocols, particularly cluster-based ones, have been developed with the potential to significantly increase network lifetime. However, these protocols still have drawbacks, such as reliance on probabilistic and centralized clustering mechanisms, single-hop communication within clusters, periodic re-clustering, and static round lengths. To address these issues, this paper presents the Distributed Energy-Efficient Clustering Routing Protocol with a Dynamic Round Length (DEECRP-DRL) for WSNs. To deal with the hotspot problem, a clustering fitness function is defined to determine the optimal Cluster Heads (CHs) and to form unequal clusters based on residual energy, intra-cluster distance, and inter-cluster distance metrics. Meanwhile, a routing fitness function is used to select the best relay nodes for efficient multi-hop data routing. The round duration is dynamically calculated based on the residual energy of CHs to minimize the overhead caused by the re-clustering process. The simulation results using OMNeT++ show that DEECRP-DRL outperforms existing algorithms across various scenarios, including the impact of Base Station (BS) location and network scalability.